Research and development of the small vertical axis wind turbine with moving blades related to wind direction - Dang, Thiện Ngôn; Phung, Tấn Lộc (Journal of Technical Education Science, 2016)
Small vertical axis wind turbine (VAWT), which can operate under small velocity (v < 6 m/s), is an issue that is being researched to develop further. A lot of solutions have been suggested such as using light material for blades and other structures, increasing efficiency of dynamo, using bearings having small friction coefficient, moving blades related to wind direction, etc. This study aims at the solution of moving blades related to wind direction, which bases on the eccentricity of wind vane’s axis and VAWT’s rotating axis. A moving blade structure automatically adjustable to follow wind direction with calculated eccentricities 45, 50, 55 and 60 mm are designed and experimented. The results show that in eccentricity value of 50 mm which makes the small VAWT utilizing NACA airfoil type operate at wind velocity of about 2.5 m/s.